1990
DOI: 10.1037/1040-3590.2.3.231
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms among American Indian adolescents: Psychometric characteristics of the Center for Epidemiologic Studies Depression Scale (CES-D).

Abstract: The psychometric characteristics of the Center for Epidemiologic Studies Depression Scale (CES-D) were investigated with American Indian boarding school students (A' = 188; Grades 9-12). The CES-D showed good internal consistency (a = .82). Its dimensional structure was different from that described for adults, both Indian and non-Indian. Of the Indian students, 58% were classified as depressed, using the standard cutoff score of 16 or more, consistent with past studies of this age group. Alternative scoring m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
77
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(81 citation statements)
references
References 37 publications
4
77
0
Order By: Relevance
“…For adolescents, these types of chronic stresses are often manifested in their day-to-day interactions with peers and family members. Consistent with this idea, American Indian adolescents rank family, relationship, and peer problems among the most stressful events in their lives~Ackerson, Dick, Manson, Beals, Dick, & Duclos, 1989;Manson, Ackerson, Dick, Baron, & Fleming, 1990!. Moreover, interpersonal stress has been identified as a risk factor for suicide in Native American youths~Ross & Davis, 1986;Dinges & Duong-Tran, 1993!, and stressful interpersonal and daily life events predict significant variance in patterns of comorbidity of psychological disorders among American Indian and Alaska Native youths~Dinges & Duong-Tran, 1993!.…”
mentioning
confidence: 81%
“…For adolescents, these types of chronic stresses are often manifested in their day-to-day interactions with peers and family members. Consistent with this idea, American Indian adolescents rank family, relationship, and peer problems among the most stressful events in their lives~Ackerson, Dick, Manson, Beals, Dick, & Duclos, 1989;Manson, Ackerson, Dick, Baron, & Fleming, 1990!. Moreover, interpersonal stress has been identified as a risk factor for suicide in Native American youths~Ross & Davis, 1986;Dinges & Duong-Tran, 1993!, and stressful interpersonal and daily life events predict significant variance in patterns of comorbidity of psychological disorders among American Indian and Alaska Native youths~Dinges & Duong-Tran, 1993!.…”
mentioning
confidence: 81%
“…Summing all items yields one overall score ranging from 20 to 80 that reflects depressive symptom severity (present sample α = .84). This scale has been well-validated in different samples of Aboriginal adolescents (Manson, Ackerson, Dick, Barón, & Fleming, 1990;Thrane, Witbeck, Hoyt, & Shelley, 2004).…”
Section: Methodsmentioning
confidence: 98%
“…These findings usually have been attributed to distress associated with minority group membership (Atkinson et al, 1998). Other studies have observed minimal or no differences in the level of depressive symptoms reported by minority and nonminority adolescents (Manson, Ackerman, Dick, Baron, & Fleming, 1990;R. Roberts, Chen, & Solovitz, 1995).…”
Section: Dual Ethnic Status and Depressionmentioning
confidence: 95%